SACRIFICING FOR THE GREATER GOOD - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
Aidil Adha greetings to everyone. A celebration that’s truly significant to the Muslim community, not just to those on pilgrimage in Makkah AlMukarramah but also to all Muslims throughout the world. We are to celebrate Aidil Adha in full of selfintrospection.